Electron–Electron Interaction and Weak Antilocalization Effect in a Transition Metal Dichalcogenide Superconductor. Issue 5 (13th February 2022) - Li, Chushan; Boubeche, Mebrouka; Zeng, Lingyong; Ji, Yi; Li, Qixuan; Guo, Donghui; Zhu, Qizhong; Zhong, Dingyong; Luo, Huixia; Wang, Huichao
Abstract : In disordered transition‐metal dichalcogenide (TMD) superconductor, both the strong spin‐orbit coupling (SOC) and the disorder show remarkable effects on superconductivity. However, the features of SOC and disorder are rarely detected directly. Herein, the quantum transport behaviors arising from the interplay of SOC and disorder in the TMD superconductor 1T‐NbSeTe are reported. Before entering the superconducting state, the single crystal at low temperature shows a resistivity upturn, which is T 1/2 dependent and insensitive to the applied magnetic fields. The magnetoresistance (MR) at low temperatures shows an H 1/2 dependence at high magnetic fields. The characteristics are in good agreement with the electron–electron interaction (EEI) in a disordered conductor. In addition, the upturn changes and MR at low magnetic fields suggest the contribution of the weak antilocalization (WAL) effect arising from the strong SOC in the material. Moreover, the quantitative analyses of the transport features in different samples imply anomalous disorder‐enhanced superconductivity that needs to be further understood. The results reveal the disorder‐enhanced EEI and the strong SOC‐induced WAL effect in 1T‐NbSeTe, which illustrates the resistivity minimum in the widely studied doped superconductors. The work also provides insights into the disorder effect on superconductivity. Abstract : Quantum transport properties of the transition‐metal dichalcogenide superconductor 1T‐NbSeTe are investigated. The single crystal shows a resistivity upturn at low temperatures before entering the superconducting state. The characteristics of the upturn and the magnetoresistance behavior reveal disorder‐enhanced electron–electron interaction and strong spin‐orbit coupling‐induced weak antilocalization effect. In addition, the material shows anomalous disorder‐enhanced superconductivity, calling for further understanding.